Perbaikan Citra Tanda Tangan Digital Menggunakan Metode Otsu Thressholding dan Sauvola - Dessy Tri Anggraeni; Condro Wibawa (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Abstract : The digital era forces people to digitize in all fields. Digital product that is often found is digital image. One kind of digital image application is the use of a digital image signature embedded in a document. However, often the results are unsatisfactory, such as background color problems, noise, lack of clarity, etc. The quality of digital image signatures can be improved by implementing the Otsu Thresholding and Sauvola methods. These two methods were chosen because they are widely used in document image quality improvement. The purpose of this study is to produce a better digital image signature and to compare the performance of these two methods. The results showed that the quality of the images produced by these two methods was better than the original image or by using standard filters from a word processing application. Meanwhile, from the two methods used, Sauvola's method was slightly better than Otsu's method. In terms of visual evaluations, the Sauvola method total score is 13 compare to Otsu method score that is 11. Meanwhile, the PSNR ratio show that the two methods give the same results, that is 34,571 db.